MELK-T1, a small-molecule inhibitor of protein kinase MELK, decreases DNA-damage tolerance in proliferating cancer cells. Issue 6 (13th November 2015) - Beke, Lijs; Kig, Cenk; Linders, Joannes T. M.; Boens, Shannah; Boeckx, An; van Heerde, Erika; Parade, Marc; De Bondt, An; Van den Wyngaert, Ilse; Bashir, Tarig; Ogata, Souichi; Meerpoel, Lieven; et al.
Abstract : Protein kinase MELK has oncogenic properties and is highly overexpressed in some tumors. In the present study, we show that a novel MELK inhibitor causes both the inhibition and degradation of MELK, culminating in replication stress and a senescence phenotype. Abstract : Maternal embryonic leucine zipper kinase (MELK), a serine/threonine protein kinase, has oncogenic properties and is overexpressed in many cancer cells. The oncogenic function of MELK is attributed to its capacity to disable critical cell-cycle checkpoints and reduce replication stress. Most functional studies have relied on the use of siRNA/shRNA-mediated gene silencing. In the present study, we have explored the biological function of MELK using MELK-T1, a novel and selective small-molecule inhibitor. Strikingly, MELK-T1 triggered a rapid and proteasome-dependent degradation of the MELK protein. Treatment of MCF-7 (Michigan Cancer Foundation-7) breast adenocarcinoma cells with MELK-T1 induced the accumulation of stalled replication forks and double-strand breaks that culminated in a replicative senescence phenotype. This phenotype correlated with a rapid and long-lasting ataxia telangiectasia-mutated (ATM) activation and phosphorylation of checkpoint kinase 2 (CHK2). Furthermore, MELK-T1 induced a strong phosphorylation of p53 (cellular tumour antigen p53), a prolonged up-regulation of p21 (cyclin-dependent kinase inhibitor 1) and a down-regulation of FOXM1 (Forkhead Box M1) target genes. Our data indicate that MELK is a key stimulator of proliferation by its ability to increase the threshold for DNA-damage tolerance (DDT). Thus, targeting MELK by the inhibition of both its catalytic activity and its protein stability might sensitize tumours to DNA-damaging agents or radiation therapy by lowering the DNA-damage threshold.